If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 2x + (x + -12) = 180 Reorder the terms: x + 2x + (-12 + x) = 180 Remove parenthesis around (-12 + x) x + 2x + -12 + x = 180 Reorder the terms: -12 + x + 2x + x = 180 Combine like terms: x + 2x = 3x -12 + 3x + x = 180 Combine like terms: 3x + x = 4x -12 + 4x = 180 Solving -12 + 4x = 180 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + 4x = 180 + 12 Combine like terms: -12 + 12 = 0 0 + 4x = 180 + 12 4x = 180 + 12 Combine like terms: 180 + 12 = 192 4x = 192 Divide each side by '4'. x = 48 Simplifying x = 48
| -(8y+2)-(7y-5)=-1 | | 9-1/2(3n-6)=n+2 | | 20n+4=24n-40 | | 2b+4=9+3b | | 5(x-2)=10(2-x) | | 0=z^2-(1+2i)z-x+2i | | 1+6x+3=5x+2 | | 0.5x^2-6=x^2+4x | | 4x+8+3x+9=13 | | f=-9+16 | | 15-8*2+12= | | -7p-4=-2p-14 | | 2[4-2(3-x)]-1=4[2(x-3)+7]-25 | | 99-4b=-11b | | 1+1+7a+3=a-1+4a | | .75k-.75=7 | | -8+b=4 | | x*5=x+4 | | 5x+45-3x=15 | | x+(x+5)+x+(x+5)=86 | | 2.25-.25g=.50g | | 5x+45+3x=15 | | 23x^2+22x=0 | | s^2=18-3s | | X+x+5+x+x+5=86 | | 23x+22x=0 | | (8p+4)+(9p+9)= | | 3+x=-8 | | a/5-1/5=-5 | | 1x+2=1x+3 | | 23.0*432*19= | | 9r^2+3r-30=0 |